A comparative study between new proposed Technique (LPAM) and the other existing techniques to Find IBFS for Transportation Problem - Alforjani Ali Ahmed, Abdussalam Ali Ahmed (Journal of Pure & Applied Sciences, 2020)
Transportation model is a special case of linear programming problem in which the main objective is to transport raw material, or finished products are transported from warehouses to factories or vice-versa, at a total minimum cost. Finding an initial basic feasible solution is the basic requirement to acquire an optimal solution for the transportation problems. In this study, a new technique named (LPAM- Technique) (The Largest penalty and allocate the maximum- technique) is proposed to locate initial basic feasible solution for transportation problems. The performance of the (LPAM) is evaluated and compared with the existing techniques in the literature (NWCM, LCM, VAM, CVAM, iLCM), To clarify the statement, The the applications twenty randomly chosen an available in the literature to Obtain (IBFS) of Transportation Problem. Obtained results show by using this technique we found that (IBFS) of most of the transportation problem very close to optimal solution or same as optimal solution than using the other existing techniques which is discussed in this study, and it is observed that the performance of proposed technique is suitable for solving transportation problems.